Specific mosaic KRAS mutations affecting codon 146 cause oculoectodermal syndrome and encephalocraniocutaneous lipomatosis. Issue 4 (29th April 2016) - Boppudi, S.; Bögershausen, N.; Hove, H.B.; Percin, E.F.; Aslan, D.; Dvorsky, R.; Kayhan, G.; Li, Y.; Cursiefen, C.; Tantcheva‐Poor, I.; Toft, P.B.; Bartsch, O.; et al.
Abstract : Abstract : Oculoectodermal syndrome (OES) and encephalocraniocutaneous lipomatosis (ECCL) are rare disorders that share many common features, such as epibulbar dermoids, aplasia cutis congenita, pigmentary changes following Blaschko lines, bony tumor‐like lesions, and others. About 20 cases with OES and more than 50 patients with ECCL have been reported. Both diseases were proposed to represent mosaic disorders, but only very recently whole‐genome sequencing has led to the identification of somatic KRAS mutations, p.Leu19Phe and p.Gly13Asp, in affected tissue from two individuals with OES. Here we report the results of molecular genetic studies in three patients with OES and one with ECCL. In all four cases, Sanger sequencing of the KRAS gene in DNA from lesional tissue detected mutations affecting codon 146 (p.Ala146Val, p.Ala146Thr) at variable levels of mosaicism. Our findings thus corroborate the evidence of OES being a mosaic RASopathy and confirm the common etiology of OES and ECCL. KRAS codon 146 mutations, as well as the previously reported OES‐associated alterations, are known oncogenic KRAS mutations with distinct functional consequences. Considering the phenotype and genotype spectrum of mosaic RASopathies, these findings suggest that the wide phenotypic variability does not only depend on the tissue distribution but also on the specific genotype.